Electric motors three phase - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with three-phase AC motor operation, inspection, testing, and maintenance. After completing this unit, trainees should be able to explain the basic principles of three-phase AC motor operation, how to inspect one, and how to conduct electrical tests on one. They should also be able to explain how to disconnect, disassemble, clean, reassemble, and reconnect a three-phase AC motor.
Keywords: Electric motors; Electric controllers